Large-scale plasma metabolome analysis reveals alterations in HDL metabolism in migraine. (16th April 2019) - Onderwater, Gerrit L.J.; Ligthart, Lannie; Bot, Mariska; Demirkan, Ayse; Fu, Jingyuan; van der Kallen, Carla J.H.; Vijfhuizen, Lisanne S.; Pool, René; Liu, Jun; Vanmolkot, Floris H.M.; Beekman, Marian; Wen, Ke-xin; et al.
Abstract : Objective: To identify a plasma metabolomic biomarker signature for migraine. Methods: Plasma samples from 8 Dutch cohorts (n = 10, 153: 2, 800 migraine patients and 7, 353 controls) were profiled on a 1 H-NMR-based metabolomics platform, to quantify 146 individual metabolites (e.g., lipids, fatty acids, and lipoproteins) and 79 metabolite ratios. Metabolite measures associated with migraine were obtained after single-metabolite logistic regression combined with a random-effects meta-analysis performed in a nonstratified and sex-stratified manner. Next, a global test analysis was performed to identify sets of related metabolites associated with migraine. The Holm procedure was applied to control the family-wise error rate at 5% in single-metabolite and global test analyses. Results: Decreases in the level of apolipoprotein A1 (β −0.10; 95% confidence interval [CI] −0.16, −0.05; adjusted p = 0.029) and free cholesterol to total lipid ratio present in small high-density lipoprotein subspecies (HDL) (β −0.10; 95% CI −0.15, −0.05; adjusted p = 0.029) were associated with migraine status. In addition, only in male participants, a decreased level of omega-3 fatty acids (β −0.24; 95% CI −0.36, −0.12; adjusted p = 0.033) was associated with migraine. Global test analysis further supported that HDL traits (but not other lipoproteins) were associated with migraine status. Conclusions: Metabolic profiling of plasma yielded alterations in HDL metabolism in migraine patients and decreased omega-3 fatty acids only in male migraineurs.